How newspapers work - Nash, W. Roy (Commonwealth and international library of science, technology, engineering and liberal studies. Liberal studies division, 1964)
How Newspapers Work is a detailed account of how newspapers work, with emphasis on the mechanics of news gathering and tasks of the reporter, sub-editor, news specialists, and editor. A typical day in the life of a morning newspaper is described, and the role of the press in society is examined.